Zones Localization of Hazardous Geological Processes Habit of the Coastal Cliff According to 3D Seismotomography Sounding Data - Glazunov Vladimir Vasil'evich; Efimova Natal’ia; Zelikman Danil; Bukatov Andrei (Russian Journal of Earth Sciences, 2025)
The article presents a methodology for conducting 3D seismic tomography of rock massifs. This technique has been developed for the identification and localisation of zones of development of dangerous geological processes formed within the rock massif of a coastal cliff. An example of the application of the technique is provided by the results of seismic tomography, which were used to study the state of a coastal cliff in Crimea that is subject to abrasion. The seismic tomographic inversion process has been utilised to generate maps depicting the distribution of 𝑃 and 𝑆 velocity values of seismic waves within the rock massif at varying depths. Furthermore, the dynamic moduli of elasticity, which are indicative of the physical and mechanical properties of the rocks constituting the cliff, have been calculated. The maps that have been generated by the seismic tomographic inversion process reflect the spatial distribution of these parameters, and the maps also localise the zones that have been weakened, presumably as a consequence of the formation and development of negative geological processes that are dangerous for the cliff's stability.